Enhancing formability of Ti-6Al-4V cylindrical cups by pulsating hydroforming process: Experimental, numerical and microstructural investigations - Ozturk, Osman; Aydin, Mevlut; Gokcepinar, Omer Faruk; Ilbeyli, Harun Mert; Korkmaz, Habip Gokay; Yapan, Yusuf Furkan; Dilmec, Murat; Halkaci, Huseyin Selcuk; Kotan, Hasan; Livatyali, Haydar; Toros, Serkan; Turkoz, Mevlut (ELSEVIER - DIVISION REED ELSEVIER INDIA PVT LTD, 2024)
Ti-6Al-4V alloy sheet is an engineering material that is widely used due to its superior properties such as high strength-to-density ratio besides high temperature and corrosion resistance. However, its low formability at room temperature limits its wider applications. In this study, a cylindrical cup was hydroformed using a female die to examine how the pulsating effect would result under frictional conditions. Initially, finite element simulations were performed to design a proper die geometry. Next, forming tests were run on Ti-6Al-4V blanks under pressure increased monotonically and with pulsation, and microstructural analyses were performed on the formed specimens. The effects of pulsation frequency, amplitude, and base pressure on the formability were investigated. The nose radius/thickness ratio, maximum thinning, bursting pressure, and die-filling ratio measured on the specimens formed under monotonic and pulsating loadings were compared, and the improvement in the formability was demonstrated. An increase of 38.5 % in bursting pressure occurred and the nose radius of the part was decreased up to 30 % with pulsating loading. The die-filling ratio was improved from 87.9 % to 95.3 % with optimized pulsation parameters. The underlying microstructural reasons for the improved formability were elaborated using XRD, SEM, and TEM analyses.
Keywords: Pulsating Hydroforming; Ti-6Al-4V; Formability; Microstructural characterization; Sheet metal forming; DEEP-DRAWING PROCESS; BEHAVIOR; SIMULATION; OPTIMIZATION; PARAMETERS; SHEETS; Engineering